Crop specific plant growth promoting effects of ACCd enzyme and siderophore producing and cynogenic fluorescent Pseudomonas - Priyanka; Agrawal, Toshy; Kotasthane, Anil S.; Kosharia, Ashok; Kushwah, Renu; Zaidi, Najam Waris; Singh, U.S. (Springer, 2017)
Fluorescent Pseudomonas, aerobic, Gram-negative bacteria possess many traits that make them well suited as biocontrol and growth promoting agents. Our study revealed that isolates vary in mechanisms involved in the antagonist interactions against pathogen and growth stimulatory effects on host plant. Most of the potential antagonistic fluorescent Pseudomonas identified were avid iron chelators (P233, P201, 176, P76 and, P76). Wide variation in ACCd enzyme production was observed. ACCd enzyme assay tested P141 > P247 > P126, as potential ACCd enzyme producer. Cynogenic fluorescent Pseudomonas isolates P76 and P124 exerted strong inhibitory against S. rolfsii. However, another cynogenic fluorescent Pseudomonas P179 had no influence against R solani and S. rolfsii which remains unexplained. Noticeable crop specific plant growth stimulation exerted by different fluorescent Pseudomonas was observed on wheat (P124), chickpea (P72), lathyrus (P85, P216), greengram (P11), blackgram (P99, P233); bottlegourd (P248, P167); rice (P176, P247)